A PROSPECTIVE STUDY ON ABNORMAL LFT PATTERNS IN PATIENTS RECEIVING ANTITUBERCULOSIS THERAPY - A, Vijayalakshmi; G, Thanmayi; S, Jayakumari (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Identification of risk factors associated with anti-tuberculosis drug-induced hepatotoxicity (anti-TB-DIH) is important, especially in an endemic area for TB and liver disease. This study assessed the incidence and risk factors of anti-TB-DIH. Hence, the present study was designed to evaluate the abnormal liver function test (LFT) in antitubercular therapy. Methods: A total of 100 consecutive TB patients were prospectively followed up both clinically and biochemically before and during their course of anti-TB therapy with daily doses of isoniazid, rifampin, ethambutol, and pyrazinamide, or streptomycin. Results: In the study, 18-30 years 17 (17%), 31-50 years 28 (28%), 51-70 years 37 (37%), and 71-80 years 18 (18%) aged patients were found where 63 (63%) are males and 37 (37%) are females. Comparison between before treatment and 2 months treatment showed a significant increase in the level of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP), viz., 51.6±3.92, 42.7±3.21, and 129±3.2 (U/L), respectively, as compared to pre-treatment levels. Comparison between before treatment and 2 months treatment showed a significant increase in the level of AST, ALT, and ALP, viz., 51.6±3.92, 42.7±3.21, and 129±3.2 (U/L), respectively, as compared to pre-treatment levels. Comparison between before treatment and after treatment (6 months) revealed a significant increase in the level of AST, ALT, ALP and gamma glutamyl transpeptidase (GGT) viz., 59.9±3.12, 51.6±3.66, 131.6±3.2, and 61±3.2 (U/L) respectively. The total bilirubin and direct bilirubin were found between 2.1±0.9 and 0.6±0.3 mg/dL respectively, when compared with before treatment. Conclusion: Anti-TB-DIH is not uncommon, needs early recognition and treatment and is more in patients with pre-existing liver disease and lower body mass index. Keywords: Anti-tuberculosis, Liver function test, Hepatotoxicity.